The Relationship of immunoglobulin-e and tumor necrosis factor in patients with allergic rhinitis in Babylon province - Bushra Jihad Sabbar; Zenaa Abbass Ali; Tariq Hussein Mgheer (Medical Journal of Babylon)
Abstract Background: Rhinitis is defined as inflammation of the mucous membranes of the nose usually that is accompanied by swelling of the mucosa and a nasal discharge. It is caused by immunoglobulin E (IgE)-mediated reactions to inhaled allergens, smoking and alcohol use, gender, age, overweight, adoption of pets, race, educational achievement, and family history can represent a risk factor for allergic rhinitis (AR). Objectives: To find the effect of electrolytes tumor necrosis factor (TNF)-α and IgE on AR and study the influence of smoking, gender, and obesity (as a risk factor on AR) on the levels of TNF-α and IgE. Materials and Methods: Eighty subjects for this study were enrolled; 40 of those who have AR age ranged between 18 and 50 years. A control group of 40 subjects who appear to be in good health was selected. This study is a case–control study. TNF-alpha concentration and immunoglobulin-E were measured in serum by an enzyme-linked immunosorbent assay (ELISA) technique also The electrolytes concentrations were measured in the serum using an Abbott device with Integrated Chip Technology (ICT) human kit. The electrolytes were also measured in the serum using the Abbott device. Full history was taken from all patients, which include age, residence, smoking, body mass index, and family history of AR. Results: The results reveal a significant difference (P < 0.05) in levels of TNF-α, Ig-E between patients and controls, There was no significant difference between smoker and non- smoker, normal weight and overweight groups in patients and controls groups.